2014
DOI: 10.3174/ajnr.a4026
|View full text |Cite
|
Sign up to set email alerts
|

Transforaminal versus Intra-Articular Facet Corticosteroid Injections for the Treatment of Cervical Radiculopathy: A Randomized, Double-Blind, Controlled Study

Abstract: BACKGROUND AND PURPOSE:Transforaminal corticosteroid injections can be performed in the management of cervical radiculopathy but carry the risk of catastrophic complications. This study compares the efficacy of transforaminal and facet corticosteroid injections at 4 weeks' follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 21 publications
2
23
0
Order By: Relevance
“…19,21 Percentage change could not be calculated from the presented data in one. 22 Bureau et al, 19 Bise et al, 21 and Kumar and Gowda 23 also reported NDI before and after CTFESI, showing 12.8%, 18%, and 35.2% improvement, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…19,21 Percentage change could not be calculated from the presented data in one. 22 Bureau et al, 19 Bise et al, 21 and Kumar and Gowda 23 also reported NDI before and after CTFESI, showing 12.8%, 18%, and 35.2% improvement, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…21-23 Quality appraisal of the included studies is summarized in Table I. Regarding randomization protocols of the RCTs, simple randomization by random-number table was used in one, 18 block randomization in one, 19 and an unspecified method in one. 20…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, among steroid injection, facet injection has been suggested to be more effective and safer than transforaminal injection. 41 The combination of bupivacaine and betamethasone has also been shown to achieve better response rates than using bupivacaine alone. 42 Autotraction seems to perform better with regard to traction pain relief compared to conventional passive traction methods.…”
Section: Discussionmentioning
confidence: 99%
“…noted the “catastrophic complications” that may be seen with cervical ESI (BUREAU 2014). [4] To minimize these risks, they designed a 4-week randomized double blind controlled study to compare the safety/efficacy for cervical intrafacet steroid injections (noted to have fewer AE (Adverse Events)) vs. TFESI. Twenty-eight patients had facet injections alone vs. 28 who underwent cervical CT-fuided TFESI; facet injections significantly reduced the pain score by 45.3% vs. TFESI that showed a “nonsignificant” pain score reduction of just 9.8%.…”
Section: Cervical Epidural Spinal Injectionsmentioning
confidence: 99%